THE INFFULENCE OF JOB SATISFACTON AND WORK DISCIPLINE TOWARDS WORK PERFORMANCE AT CV. JAYA MOTOR SEMARANG - Fajar Wali Haryo Legowo; Rodhiyah Rodhiyah; Sari Listyorini (Universitas Diponegoro, 2012)
The success of an organization in achieving the objectives that have been set are determined by the quality of the people who work in it or that we call with top management, middle management, and line management as well as the usual non managerial we call with employees. In an organization or company, we often hear the term job satisfaction, work discipline in which both these factors is one of the causes of poor performance or deciding whether an employee's work. The question in this research is whether there are effects of job satisfaction of Accomplishment Work, is there any influence of the discipline of work against the Working Achievements, as well as whether there are effects of job satisfaction and Work towards the Accomplishment of work Discipline. Type this research is explanatory research that is research that observing the relationship between variables and test the hypothesis that has been formulated. The technique of collecting data use sampling saturates ( census ) with the population is all the employees CV. Jaya Motor Semarang of 45 people. Test the validity of, using data analysis test reliabilities, linear regression simple, worship of idols, linear regression a coefficient determination, test t, test f, with the help of program SPSS for windows version 17. The result of the research is as follows: There is a significant positive influence between satisfaction work on work performance where t count as much as ( 10.972 ) > t a table ( 1,680 ), and there is a significant positive influence between discipline work on work performance where t count as much as ( 7.454 ) > t a table ( 1,680 ). There is a significant positive influence between satisfaction of work and discipline work on work performance where f count ( 70.579 ) > f a table ( 3.220 ). A coefficient determination to variable satisfaction work ( X1 ) and discipline work ( X2 ) accounts for as much as 77.1 % for the work performance while 22.9 % influenced by other factors. Based on the research inconclusive satisfaction of work and discipline work have leverage significantly to work performance so that hypothesis accepted. Means if satisfaction of work and discipline work offered better, then work performance will increase. While companies to set satisfaction work is more like to fit the purchasing power of consumers. Advice given to CV. Jaya Motor Semarang is in giving maximum service to consumers, should increase response will complaints, so can increase consumer confidence to business. Company can also provides opportunities to employees to in education and exercises about service the car, held by inside and outside country.